2008
DOI: 10.12806/v7/i1/rf5
|View full text |Cite
|
Sign up to set email alerts
|

What Do They Need? Intrinsic Motivation and Online Leadership Learning

Abstract: Education, training, and development involve different kinds of activities and result in quite different outcomes. An ideal program to create leaders should incorporate all three: educating participants to provide a knowledge base, training them to acquire the desired skills, and assisting them in developing insight into their own beliefs and values and their effect on others.Education is the most academically legitimate when compared to training or development. The transfer of information and knowledge from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Yet, amid all the conversations and research related to leadership education, there is little, if any, mention of effective pedagogical incorporation of technology. Only a few studies have investigated instructional strategy use in online leadership education generally (e.g., Boyd & Murphrey, 2001;Cini, 1998;Jenkins, Endersby, & Guthrie, 2015;McCotter, 2008;Newberry, Culbertson, & Carter, 2013;Phelps, 2012;and Saks, 2009) or with respect to specific online instructional techniques such as discussion boards (Dollisso, 2011), blogs (Gifford, 2010;Giraud, Cain, Stedman, & Gifford, 2011), service learning (Guthrie & McCracken, 2010), social media (Odom, Jarvis, Sandlin & Peek, 2013;Steves, Keen, Hooker, Keane, Needles, & Fuess, 2011), and simulation (Weeks, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, amid all the conversations and research related to leadership education, there is little, if any, mention of effective pedagogical incorporation of technology. Only a few studies have investigated instructional strategy use in online leadership education generally (e.g., Boyd & Murphrey, 2001;Cini, 1998;Jenkins, Endersby, & Guthrie, 2015;McCotter, 2008;Newberry, Culbertson, & Carter, 2013;Phelps, 2012;and Saks, 2009) or with respect to specific online instructional techniques such as discussion boards (Dollisso, 2011), blogs (Gifford, 2010;Giraud, Cain, Stedman, & Gifford, 2011), service learning (Guthrie & McCracken, 2010), social media (Odom, Jarvis, Sandlin & Peek, 2013;Steves, Keen, Hooker, Keane, Needles, & Fuess, 2011), and simulation (Weeks, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, several stakeholders such as academic heads, teachers, and students were mentioned. In articles focused on online leadership programmes, the primary stakeholders identified were the participants of the programmes such as students, teachers, educational leaders, and health care professionals (Fernandez et al, 2021;Hayes and Irby, 2020;McCotter, 2008). Research addressing the leadership development due to online learning and teaching focused on either group (study groups/ teams) (Moore, 2008) or individual stakeholders (students and teachers) (Ellis et al, 2017;Kim et al,2020).…”
Section: Stakeholders and Leadersmentioning
confidence: 99%
“…We believe that students enter with a high intrinsic motivation to participate when the program is seen as an exclusive opportunity. McCotter (2008) observed "when students are intrinsically motivated, they are more likely to be engaged in their learning and also to achieve high standards" (p. 96). She added that participants "will be motivated to engage in tasks that are perceived to have value for their future," concluding that if they "want to do something and feel as if they will be successful, they are likely to be motivated during the task" (p. 96).…”
Section: Structure and Deliverymentioning
confidence: 99%
“…How we answered these questions determined the nature of the program. McCotter (2008) observed that "online and hybrid classes have become common in the fields of leadership education" (p. 92). Moreover, the explosion of e-learning across curriculum areas had propelled News University's 10 years of significant growth.…”
Section: Structure and Deliverymentioning
confidence: 99%